EMHD hybrid squeezing nanofluid flow with variable features and irreversibility analysis. (21st January 2022) - Ramzan, Muhammad; Riasat, Saima; Alotaibi, Hammad
Abstract: This study discusses the entropy generation analysis of electro-magneto hydrodynamics (EMHD) hybrid nanofluid copper oxide-aluminum oxide/ethylene glycol (CuO–Al2 O3 /C2 H6 O2 ) flow amidst two rotating disks in a porous media having variable thermophysical features. The addition of the surface catalyzed to the homogeneous-heterogeneous reactions shorten the reaction time that may be taken as a novel aspect of the undertaken EMHD hybrid nanofluid squeezing flow. The inimitability of the assumed model is supplemented by considering the simultaneous effects of the variable thermal conductivity and viscosity. To simplify the governing flow model, suitable conversions are used to accurately translate the obtained partial differential equations to ordinary differential equations. The flow and energy transfer characteristics are computed and sketched graphically by using the Keller box scheme. The outcomes reveal that the drag force in radial and tangential directions depict the opposing trend for variable viscosity parameter. Furthermore, the normal magnetic and transverse electric fields play an essential role in the alignment of the nanoparticles throughout the flow field. The validation of the envisaged model is also a part of this study.